FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN CAKUPAN BALITA DI TIMBANG (D/S) DI POSYANDU WILAYAH KERJA PUSKESMAS BETUNG - Pratiwi Rahmadhani, Sendy; Larasati, Ayu; Aquari, Bina; Minata, Fika (JURNAL KESEHATAN INDRA HUSADA, 2024)
Monitoring the weight of toddlers monthly at Posyandu is an indicator related to the coverage of basic health services especially the prevalence of malnutrition in toddlers, early detection and preventing growth and development failure in toddlers. The aim of this study is to determine the relationship between the role of health workers, mother’s attitude, and the quality of service on the coverage of toddlers being weighed (D/S) in Betung Community Health Centre working area. This study uses an analytical survey method and a crosssectional approach. The population of the study was mothers who had toddlers with a tota) number of 101 toddlers in Betung Community Health Centre working area. The sample of this study included 50 toddlers taken by using accidental sampling technique. The data were analysed by using chi-square test. Univariate analysis showed that toddlers with low coverage of toddlers weighed (D/S) were 18 respondents (34%), while toddlers with D/S with high coverage were 32 respondents (66%). The result of bivariate analysis showed that there were significant relationships between the role of health workers (P-value was 0,047), mothers’ attitude (P-value was 0,001), the quality of service (P-value was 0,000) and the coverage of toddlers weighed (D/S) in Betung Community Health Centre working area. The conclusion is there is a significant relationship between the role of the health workers, mother’s attitude, and the quality of service on the coverage of toddlers weighed (D/S). It is hoped that mothers will be more consistent in monitoring the toddlers’ weight every month.